Predifining emotion through product design - Reni, Theresia; Hudrasyah, Herry (SBM ITB, 2010)
In the recent decades the business environment has changed tremendously due to the advance of globalization and competition, changing the essentials for success. To overcome competitive pressure, marketer and designer have to focus on customer's sensory needs and desires to create a deep rooted relationship through emotional dialogue. In this context, innovativeness appears to be a key ingredient to create and control consumer's emotion. Perceived of innovativeness is strongly influenced by consumer desire attribute of product. Design innovativeness is one of a powerful differentiator, which can be used as a strategic tool to achieve and sustain competitive advantages. Design's contribution to a product's success manifests itself in several ways, for example in packaging design. Packaging is a tool to build emotional connectivity with consumer. Marketer and designer have to be creative to build deep relationship with consumer through aesthetics and visual attribute of packaging design, in this case : cosmetics packaging. This study attempts to show that perceived innovativeness which are build from consumer's visual standard are important aspect in building emotional responses. Collecting method in this research is using questionnaire Population in this research is working woman in Jakarta, sample amounting to 102 people. Hypothesis examination in this research by correlation and multiple regression. Analysis result indicate that perceived innovativeness and consumer's visual standard have an effect to emotional elicited.Keywords: Perceived Innovativeness, Consumer's visual standard, Emotional elicited